Riparian Vegetation Structure in a Conservation Unit in the Semi-Arid Region of Paraíba, Brazil - Lacerda,Alecksandra Vieira de (2020)
Abstract This study aimed to carry out a phytosociological survey in a riparian area of an intermittent stream in the semi-arid region of Paraíba, Brazil. Fifty-one contiguous plots of 10 × 20 m (1.02 ha) were distributed along the watercourse. Living and dead shrub-tree individuals, still standing, with stem diameter at ground level (DGL) ≥ 3 cm and total height ≥ 1 m were sampled. Fifty-one species distributed in 22 families were sampled. Fabaceae, Euphorbiaceae, and Anacardiaceae had the highest species richness. Aspidosperma pyrifolium Mart. & Zucc., Combretum monetaria Mart., and Cenostigma pyramidale (Tul.) E. Gagnon & G.P. Lewis had the highest importance values. Shannon index was 2.61 nats.ind.−1 and the total basal area was 25.4 m2. Height and diameter mean values were 5.4 m and 12.4 cm, respectively. Phytosociological parameters recorded for the studied riparian vegetation have higher values in comparison with those obtained in other areas of the caatinga.